Ecos cinematográficos na poesia de Carlos Drummont de Andrade - SANTOS, Glleyce Clívia Vinagre (Universidade Federal do Pará, 2019)
The present dissertation develops an interpretive proposal of the changes occurred in the twentieth century, regarding human perception and its relation with a poetic language when it makes the movie of the cinema and the mark this in the poetry production of Carlos Drummond de Andrade, both in the which refers to references to cinema or to the use of a cinematographic language as a form of renewal of literary language for the influences in the formation of the drummondiano lyrical subject. Thus, divided into three chapters, poems selected from Alguma poesia (1930), "Canto ao homem do povo Charlie Chaplin", from A rosa do povo (1945), and a selection of poems from the series Boitempo (1968, 1973 and 1979). In the first chapter we see the outline of a panorama that clarifies us about a cinematographic language, such as changes in the structure of human perception when the emergence of cinema in modern man's life and his mark on Drummond's poetry. The second chapter introduces a reading of Drummond poems to investigate his profile as a poet-cinematographer and a transposition of a cinematographic language into a poetic language. In the third and last chapter are revealed some links between a drummondiana poetry and the Charlie Chaplin films, as well as some affinities between the poetic subject Carlos and the film character Carlito. Among the main theoretical and critical references taken as a basic for the writing of the chapters are Walter Benjamin (1987), with regard to the brand of cinema in human perception, Andrei Tarkovski (2010), in the treatment of cinematographic aspects, Paul Ricoeur (2007) and Henri Bergson (1999), with regard to the apprehension of memories in images, André Bazin (2006) in the study of aspects of the chapliniana work, finally, Marlene de Castro Correia (2002, 2010 and 2015), Davi Arrigucci Jr. (2002) and Antonio Candido (1989 and 1995) for the oriented study of the poetry of Carlos Drummond de Andrade.